1975
DOI: 10.1084/jem.141.3.697
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of delayed-type hypersensitivity by doses of cyclophosphamide which do not affect antibody responses.

Abstract: Immunization of mice with low doses of sheep red blood cells (SRBC) which are suboptimal for antibody responses, leads to sensitization for delayed foot pad reactions within 4 days (1-3) . These delayed-type hypersensitivity (DTH) reactions cannot be elicited in mice which have been immunized with larger doses of SRBC that are more optimal for antibody responses (3, 4) . It has been suggested that B-cell responses to high dose immunization cause suppression of T-cell-mediated delayed foot pad reactions (3) . I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
119
2

Year Published

1978
1978
1988
1988

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 375 publications
(128 citation statements)
references
References 11 publications
7
119
2
Order By: Relevance
“…There are three major ways to favor this skewing: (a) Pretreat the animals with a low dose of CY before their initial contact with antigen. CY, in the dose used, has been shown to inhibit cells in the suppressor T-cell circuit (11,12). Our results in this case contrast with the findings of Miller et al (13).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…There are three major ways to favor this skewing: (a) Pretreat the animals with a low dose of CY before their initial contact with antigen. CY, in the dose used, has been shown to inhibit cells in the suppressor T-cell circuit (11,12). Our results in this case contrast with the findings of Miller et al (13).…”
Section: Discussioncontrasting
confidence: 57%
“…As has been noted previously (3,11), this occurs when initial immunization with TNP-conjugated cells occurs in the spleen via intravenous injection of hapten-conjugated ceils. There is no requirement for major histocompatibility complex (MHC) identity between the haptenated cells and the host for this form of specific immunosuppression to occur, and presentation need not be on macrophages.…”
Section: Discussionmentioning
confidence: 85%
“…However, different timings and doses of drug reduced T-cell cytotoxicity. Askenase et al (1975) showed an increase in delayed hypersensitivity reactions to sheep red cells when mice were tested 10 days after receiving 20 mg/kg of Cyclo. These mice had been given a primary immunization the day after the drug.…”
Section: Resultsmentioning
confidence: 99%
“…There are several the combined effects of anti-tumour im-ways in which synergy between drug munity and cytotoxic drugs (Mihich, treatment Fisher et at., 1975). However, in tumour cells; (2) drugs may actually some instances it has been difficult to potentiate cytotoxic immunity by indistinguish the cytotoxic effect of the terfering with regulatory mechanisms drug on the tumour from the effect of (Askenase et al, 1975;Otterness and Chang, 1976) (Porteous and Munro, 1972;Chassoux et al, 1977 Heparinized Minimum Essential Medium (MEM) was injected i.p. The cell-containing medium was recovered through an abdominal incision with a Pasteur pipette.…”
mentioning
confidence: 99%
“…Since previous work has shown that cyclophos- phamide evokes an enhanced delayed hypersensitivity response to SRBC by selectively destroying B lymphocytes in the mouse (14,15), an experiment was designed to test this finding in rats. Pretreatment with cyclophosphamide was required to obtain a positive ear response 14 days after intraperitoneal sensitization with SRBC in Sprague-Dawley rats (Table 3).…”
Section: Resultsmentioning
confidence: 99%